Pengaruh Diversifikasi Program Studi Terhadap Minat Kuliah Mahasiswa Pada Universitas Islam Negeri Alauddin Makassar - Effendi, Ahmad (Al-Hikmah Journal for Religious Studies, 2014)
The aims of this research is to test and to analyze the effect of diversified courses to the college studentâs interest. This study uses primary data through a survey of 364 college studentâs as sample of all students of the faculty of Sharia, the faculty of Sciences and Technology and the faculty of Health Sciences. The survey was conducted from October to November2012. Data were analyzed using regression methods by Statistical Program for Social Science (SPSS).The results showed that brand image has appositive and significant effect to the college studentâs interest. Considering the results, the Alauddin Islamic State University must continue to innovate in the form of a diversified program of study in order to compete with competitors.